El servicio al cliente en la imagen corporativa de la compañía de transporte escolar cotranseptur de la ciudad de Puyo: periodo 2017. - Chariguamán Tustón, Diana Lizeth (2017)
The objective of this research is focused to improve the customer service in the corporate image of the transport company COTRANSEPTUR in the Puyo city in some aspects, based on the importance of generating competitive improvements at the organization level starting from the incorporation of added value to each activity to be performed by the human resource which is linked to the staging of the branding business which is associated with increasing the possibilities of competition within the Puyo market. The great impact of owning corporate branding as a letter of introduction to clients. Both occasions and headlines, and the sustainable environment at an economic and financial information that it produces. The present investigation is constituted by four chapters, the same that are developed next: Fist chapter: It is composed by the Referential framework, in which it integrates the approach of the problem, formulation of the problem, general objective and specific objectives, and justification. Chapter two: It consists of the theoretical framework; it contains background an theoretical foundation together the first unit includes an overview of the company, second unit refers to customer service and finally the third unit with regard to corporate image. Third Chapter: the methods used for this investigation, the type of research used, the processing of the information, the analysis and interpretation of results and the verification of the hypothesis are detailed. Fourth Chapter: It is composed of the conclusions and recommendations of the research, finally it will be possible to show result to the problematic raised at the beginning of the investigation.